Amarís Duarte, Olga: Una poética del exilio. Hannah Arendt y María Zambrano. Barcelona, Herder, 2021. 319 pp. - Pérez Díaz, María (Cuadernos de Historia Contemporánea, 2021)
Reseña de la obra de Amarís Duarte, Olga: Una poética del exilio. Hannah Arendt y María Zambrano. Barcelona, Herder, 2021. 319 pp.